2007
DOI: 10.1167/iovs.06-0934
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitudes, and Beliefs about Dilated Eye Examinations among African-Americans

Abstract: Study findings identified important links between financial resources and experiencing a vision problem and the adoption of preventive eye care in an urban African-American population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
59
1
5

Year Published

2009
2009
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(78 citation statements)
references
References 28 publications
6
59
1
5
Order By: Relevance
“…The self-reported factors of interest were: (1) sex (''male'' or ''female''), (2) ''$50,000-$74,999'', or ''$75,000 and greater''), (6) marital status (''married'' or ''not married''), (7) health insurance (''healthcare plan'' or ''no healthcare plan''), (8) number of mentally unhealthy days within the past 30 days (''less than 14 days'' or ''14 or more mentally unhealthy days''), (9) whether patients are now taking insulin (''yes'' or ''no''), (10) whether patients have ever taken any class in managing diabetes (''yes'' or ''no''), (11) sufficiency that patients' feet are checked by healthcare professionals annually (''sufficient'' or ''insufficient''), (12) whether patients have ever had a heart attack (''yes'' or ''no''), (13) whether patients have been told that their blood pressure is high (''yes'' or ''no''), (14) whether patients have been told that they have high cholesterol (''yes'' or ''no''), (15) whether patients have been told they have coronary heart disease/angina (''yes'' or ''no''), and (16) whether patients had a history of stroke (''yes'' or ''no'').…”
Section: Independent Variablesmentioning
confidence: 99%
See 2 more Smart Citations
“…The self-reported factors of interest were: (1) sex (''male'' or ''female''), (2) ''$50,000-$74,999'', or ''$75,000 and greater''), (6) marital status (''married'' or ''not married''), (7) health insurance (''healthcare plan'' or ''no healthcare plan''), (8) number of mentally unhealthy days within the past 30 days (''less than 14 days'' or ''14 or more mentally unhealthy days''), (9) whether patients are now taking insulin (''yes'' or ''no''), (10) whether patients have ever taken any class in managing diabetes (''yes'' or ''no''), (11) sufficiency that patients' feet are checked by healthcare professionals annually (''sufficient'' or ''insufficient''), (12) whether patients have ever had a heart attack (''yes'' or ''no''), (13) whether patients have been told that their blood pressure is high (''yes'' or ''no''), (14) whether patients have been told that they have high cholesterol (''yes'' or ''no''), (15) whether patients have been told they have coronary heart disease/angina (''yes'' or ''no''), and (16) whether patients had a history of stroke (''yes'' or ''no'').…”
Section: Independent Variablesmentioning
confidence: 99%
“…22 Other studies reported similar findings, where the most important barriers to preventive eye care were cost and lack of insurance. [15][16][17] Lack of health insurance may contribute to the lack of affordability and encumbers timeliness with diabetic dilated eye examinations. 27 Because previous reports suggest that diabetic complications and compliance are significantly related to quality of life, including mental health, 28 this study sought to find a relationship between mentally unhealthy days and the receipt of a diabetic eye examination within the last year.…”
Section: Other Independent Variablesmentioning
confidence: 99%
See 1 more Smart Citation
“…6,9,10 Barriers to care include lack of access to care, high costs, limited insurance, distance, time away from work, and difficulty with transportation. [9][10][11][12][13][14][15] Low comprehension of risk for DR, even after discussions with the provider, also leads to lack of adherence to eye screening recommendations. 6,10 In one study, 91% of patients cited ''the doctor's recommendation'' as a key reason to follow up with eye examinations.…”
Section: Introductionmentioning
confidence: 99%
“…3,9 Obtaining eye examinations from eye care providers has been problematic for minorities (compared with non-Hispanic whites) because of greater difficulty with transportation, ability to access eye care providers, co-pays and other costs of the eye examination, and/or lack of health insurance. [10][11][12] Telemedicine may increase the number of patients with diabetes who receive diabetic retinopathy screening examinations in rural and limited-access populations because it allows for rapid retinal imaging without dilation in primary care clinics. This imaging has shown excellent diagnostic precision for diabetic retinopathy compared with examinations in eye care providers' offices with dilated pupils.…”
Section: Introductionmentioning
confidence: 99%